Mobile Service Robots for Older Adults’ Mobility: Investigation of Their Attitude for Daily Assistance in Residential Environments - Vedia Durmaz; Yasemin Afacan; Parla Özkul (Senex: Yaşlılık Çalışmaları Dergisi)
Background: As the world's aging population increases, care of older adults has become inevitable. Regarding older adults’ care, mobility is the biggest struggle for older adults, whose bones and muscles deteriorate. The solution is to provide independence in built environments where older adults live and experience during their daily lives. Technological investigations raise the focus on care services within social assistive technologies. With the increasing need for older adults’ care faced by governments, understanding practical solutions is crucial for social robot development. Aim: This research aims to examine the impact of the appearance of mobile service robots, explore changes in older adults’ attitudes, and assess the potential mediating factors in the relationships between age and education. Another objective is to analyze the mobility tasks for daily life activities on the attitude of older adults towards service robots. Method: A survey design was created, with a sample of 19 from Antalya and Kocaeli, aged over 65, divided into 12 women and 7 men. First, older adults conducted a survey to elaborate on their mobility problems. Later, older adults were asked to complete another three-part survey to assess their attitudes toward mobile service robots and their daily activities. All data were collected by using self-reported questionnaires in their residential environment. These data were analyzed through descriptive analysis to create Interpersonal Circumplex. The relation between age and attitude was calculated through the Pearson Correlation. Independent Samples t-Test explored older adults’ attitudes toward service robots in daily activities. Findings: The findings revealed that the mobile service robots’ appearance affected the older adults’ attitudes, whereas age was the mediator that impacted older adults’ attitudes, unlike education. Results: Moreover, the results demonstrated that older adults having difficulty in daily activities needed more privacy and were more distant from the mobile service robots.